Cancer patient's record queries using answer on-demand data sharing architecture - Aiza Syahida, Zakaria (2014)
In medical tourism environment, one prominent concern is completeness of patients’ medical records. In this research, the concern is on the completeness of medical tourism patients’ medical records, which falls under the tuple – based completeness problem. The focus is on cancer patients whose complete medical records are highly crucial. One way to acquire complete medical records for all cancer patients is by gathering the medical records from every individual hospital. The method used is full data integration approach that provides unified view and access of data from heterogeneous data sources. In details, the proposed framework applies on - demand data sharing techniques to the architecture in medical tourism healthcare system. This results in reducing the search time and data anomalies improve the efficiency of DBMS operations, build the architecture with data integration friendly, number of data sources is counted and standardize the database product. As a support to the results gained, there are strategies on the practicality of on – demand data sharing in the process to improve completeness and access of patients’ medical records.